The Socialist Workers Party proposes : a bill of rights for working people : for protection from soaring prices, layoffs, wars, racial oppression, and sexism : Peter Camejo for president : Willie Mae Reid for vice-president. - Socialist Workers Party (SWP) (New York : SWP, 1976)
Biliotheek François Vercammen
Engels
Brochure